The Development of Reading Comprehension Skills Using the KWL PLUS Technique for Grade 9 Students at Phrapariyattidhamma Chao Phraya Bodindecha School, Yasothon Province - Sugandasiri (Kethom), Phramaha Warana; Sribunrueang, Pacharakit; Phrakrukhamphithammanuwat, (Journal of Buddhist Education and Research (JBER), 2026)
This research aimed to (1) develop a learning management plan to enhance reading comprehension skills using the KWL PLUS technique for Grade 9 students at Phrapariyattidhamma Chao Phraya Bodindecha School, Yasothon Province, with an efficiency of 80/80, (2) compare learning achievement in reading comprehension before and after implementing the plan, and (3) examine students’ satisfaction with the learning management plan. The research tools included: (1) a learning management plan using the KWL PLUS technique, (2) an achievement test on reading comprehension, and (3) a student satisfaction questionnaire. The sample consisted of 12 Grade 9 students in the second semester of the 2024 academic year. Data analysis used basic statistics: mean, standard deviation (S.D.), and dependent t-test. The research results were as follows: 1. The learning management plan showed a process efficiency (E1) of 82.50 and a result efficiency (E2) of 83.06, exceeding the established criterion of 80/80. 2. The students’ pre-test mean score was 17.30 (S.D. = 9.72), while the post-test mean was 24.90 (S.D. = 3.58). The post-test scores were significantly higher than the pre-test scores at the .05 level. 3. Student satisfaction with the learning plan was at the highest level overall (x̄ = 4.54). The instructional activities (x̄ = 4.57), assessment and evaluation (x̄ = 4.65), and instructional media and tools (x̄ = 4.50) were all rated at the highest level, while the content was rated at a high level (x̄ = 4.42).